Mānasa-mandira : mānasaśāstrācyā adyāvat siddhāntāñcī subodha carcā karūna vaiyyaktika va sāmājika jīvanāsambandhī navī drshṭi deṇārẽ pustaka - Phadke, Narayan Sitaram (SAMP early 20th-century Indian books project, 1935)
On the effects of the new experiments in psychology on people's as well as individual's life.